Whose pain is taken seriously? linguistic credibility, gendered expression, and diagnostic inequality in Indonesian clinical encounters - Sri Astutik Andayani (Indonesian Journal of Medical Linguistics, 2026)
Background: Pain credibility in clinical encounters is often shaped by language, gendered expectations, and diagnostic uncertainty, making unequal recognition of suffering a communicative as well as biomedical problem. Objective: This study examines how Indonesian public clinical communication frames pain as credible, doubtful, ordinary, urgent, or diagnostically actionable. Method: Using a corpus-assisted discourse-pragmatic design, this study analyses 25 deduplicated public documents from national health institutions, hospital sources, public campaigns, and media texts through linguistic credibility analysis, a gendered pain legitimacy matrix, and a clinical communication and language-justice audit. Results: Pain was most frequently legitimised through communication contexts, symptom recognition, treatment pathways, service access, and warning-sign language. Gendered pain gained seriousness mainly when attached to reproductive, menstrual, pelvic, sexual, fertility, or screening-related categories, indicating that women’s pain was recognised through specific biomedical thresholds rather than through gender-neutral suffering. Implication: Language access, plain explanation, informed consent, patient rights, listening, and diagnostic safety emerged as conditions through which pain testimony became clinically intelligible and actionable. Novelty: This study contributes by repositioning diagnostic inequality in pain care as an epistemic and linguistic process in which credibility, gendered expression, and communicative access jointly shape whose pain is taken seriously within Indonesian healthcare communication and patient-safety discourse contexts